Pengaruh Debt Asset Ratio, Return on Equity, Growth, dan Size terhadap Kebijakan Dividen - Desmiza Desmiza (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
Dividend policy is one of the functions of financial management, where the policy must be properly decided by a manager, so that the interests of the company and investors are balanced. This study aims to examine company-specific factors such as debt asset ratio, return on equity, growth and size that can affect the dividend payout ratio. The method used is descriptive and verification with multiple regression panel data test tools. The sample used is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2009-2016 with a total of 97 companies with 302 units of analysis. Meanwhile, the data used is in the form of secondary data sourced from the Indonesian Capital Market Directory (ICMD) and the Capital Market Reference Center. The test results found that the dividend payout ratio was significantly influenced by the debt asset ratio, return on equity and size. Unlike growth, the test results prove that growth does not affect the dividend payout ratio.